Female Cycling and the Discourse of Moral Panic in Late Victorian Britain - Kiersnowska, Beata (Atlantis. Journal of the Spanish Association for Anglo-American Studies, 2019)
This article discusses the role of cycling in women’s emancipation in late Victorian Britain and explores the attitudes of the middle-class public to women’s pursuit of this recreational activity. The unique combination of healthy physical exercise, unrestrained mobility and sporting excitement that the bicycle offered elevated cycling into one of the epoch’s most popular leisure activities. For women, the bicycle became an important instrument to break away from the constraints of the androcentric paternalistic culture that stereotyped them and cast them in the passive role of the angel in the house. The immense popularity of bicycling with middle- and upper-class women and the inevitable changes in patterns of female leisure, clothing and normative behaviour it involved, caused strong reaction from the bourgeois establishment. An analysis of opinions published in the British press at the time reveals a discourse marked by anxiety that cycling might become an avenue for women to claim more independence for themselves and even subvert the established social framework based on power relations and a clear delineation of gender roles. Keywords: women; cycling; late Victorian period; gender roles; press; prejudice